Knowledge, attitude and practice towards COVID-19 vaccination acceptance in West India - Bhartiya, Shibal; Kumar, Nishant; Singh, Tarundeep; Murugan, Sathiabalan; Rajavel, Saranya; Wadhwani, Meenakshi (International Journal Of Community Medicine And Public Health, 2021)
Background: Coronavirus disease 2019 (COVID-19) pandemic has affected more than 200 countries causing loss of life and livelihood. The accelerated development of the COVID-19 vaccine is a vital development, and early data suggests that it is both, safe and efficacious. However, the acceptance of COVID-19 vaccine depends on various socio-demographic characteristics. The aim of this study was to understand the knowledge and attitude towards COVID-19 vaccine in India. Methods: This is a cross-sectional study done in an urban slum in Mumbai, India. The main outcome variable was the responses related to COVID-19 vaccine acceptance among the study participants. Results: A total of 1342 participants were included in the study. Almost two thirds (64.5%) of the young adults aged between 18 and 40 years were unaware about the COVID-19 vaccine availability, followed by 56.4% person aged between 40 and 60 years and 46.2% of the persons aged more than 60 years were unaware about the vaccine availability. Among the study participants, nearly 79% were willing to take COVID-19 vaccine when it is available for use and only 2% did not want the vaccination. More than 2/3rd of the people who responded that they are willing to accept the COVID vaccine belong to the no income group. Conclusions: The most important factor for vaccine hesitancy is the occurrence of mild or serious adverse effects following immunization. Vaccine acceptability may be increased once additional information about vaccine safety and efficacy is available in the public domain, preferably from a trusted, centralized source of information.